Jacques Lacan and the Freudian practice of psychoanalysis - Nobus, Dany (Makers of modern psychotherapy., 2000)
Structured thematically around five key issues, Lacan's entire work, both published and unpublished material has been taken into account and theoretical examples are illustrated with clinical examples and full bibliography.